Performance Evaluation of Bentonite/Nano-SiO2 Composite as Bleaching Earth in Crude Palm Oil Processing - Agung Kurnia Yahya; Enny Nurmalasari; Apsari Puspita Aini; Hana Nikma Ulya (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
In crude palm oil (CPO) processing industries, bleaching is important to remove unwanted impurities. Most industries use various bleaching earth with 0.8-2% w/v concentration during the bleaching process. As bleaching earth is single-used for the bleaching process, materials with higher adsorption ability are preferable to reduce the use of bleaching earth. This study aimed to evaluate the performance of bentonite/nano SiO2 composite (BE-SiO2) as bleaching earth in the bleaching process of CPO. The prepared BE-SiO2 was used in the bleaching process with various BE-SiO2 concentrations (0.1-1.3% w/v), process duration (0-2.5 hours), and process temperature (70-150°C). From the results, the rise in BE-SiO2 concentration during the CPO bleaching process initially led to a decrease in the β-carotene concentration, acid content, free fatty acids (FFA), and DOBI number up to 1% w/v of BE-SiO2. Subsequently, these parameters exhibited an increase with the addition of BE-SiO2. The bleaching process effectively reduced the β-carotene concentration, acid content, FFA, and DOBI number within the first 1.5 hours of operation. While a higher amount of β-carotene was adsorbed during the adsorption process at higher temperatures, the bleached palm oil (BPO) quality was compromised due to the heat. The results showed that the most effective condition of the bleaching process was performed with 1% w/v BE-SiO2 concentration for 1.5 hours at 90°C. From those conditions, the BPO had a β-carotene concentration of 312.311 ppm, water content of 0.112%, acid number of 0.0076, FFA of 4.864%, DOBI number of 1.311, and red/yellow of 1.5/15.